IgG4-Related Lesion in Spleen: Sclerosing Angiomatoid Nodular Transformation of the Spleen. (21st September 2018) - Lu, Ying; Li, Li; Bhat, Rekha; Steve Hou, MD, J
Abstract: Objectives: Sclerosing angiomatoid nodular transformation of the spleen (SANT) is a rare benign vascular lesion of the spleen with extensive sclerosis and unknown etiology. Methods: We report a case of SANT of the spleen found in a 43-year-old African American female with a history of pancreatic neuroendocrine carcinoma status post Whipple procedure in 2014. CT scan revealed marked solid enhancing hypovascular splenic mass measuring 7 cm in 2017, suspicious for metastatic carcinoma or lymphoma. She underwent open splenectomy, and the specimen was sent for histopathologic examination. Results: Gross examination of the spleen shows a well-circumscribed mass with dark brown cut surface interspersed with whitish fibrotic stroma. Microscopic examination demonstrates a multinodular growth pattern composed of slitlike or irregular-shaped vascular space surrounded by dense collagen fibrosis. The nodules are composed of vascular channels of varying caliber lined with plump endothelium interspersed with ovoid or spindle cells. No atypia, mitotic figures, or necrosis are seen. There are abundant red blood cells admixed with fibrosclerotic or myxoid stroma with myofibroblasts, abundant plasma cells, and small mature lymphocytes. White pulp is atrophic within the mass and the splenic tissue surrounding the mass is unremarkable. CD138 highlights abundant plasma cells present, which produce IgG and IgG4 with an IgG4/IgG ratio of 0.6:1. Conclusion: The etiology of SANT is most likely a reactive process and it may be associated with IgG4-related sclerosing lesion.